2022
DOI: 10.4103/aja202221
|View full text |Cite
|
Sign up to set email alerts
|

An examination of predictive markers for successful sperm extraction procedures: a linear model and systematic review

Abstract: The authors performed a comprehensive review of current literature to create a model comparing commonly evaluated variables in male factor infertility, for example, follicle-stimulating hormone (FSH), testicular volume (TV), and testosterone (T), to better predict sperm retrieval rate (SRR). Twenty-nine studies were included, 9 with data on conventional testicular sperm extraction (cTESE) for a total of 1227 patients and 20 studies including data on microdissection testicular sperm extraction (mTESE) for a tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Recently, Major et al. conducted a multiple weighted linear regression and found that SRR decreased by 1.0% for every 1.19 mIU/mL increase in FSH 38 . Less attention has been given to the predictive value of LH for SRR, but our results showed that lower LH levels were more beneficial for sperm retrieval outcomes.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Recently, Major et al. conducted a multiple weighted linear regression and found that SRR decreased by 1.0% for every 1.19 mIU/mL increase in FSH 38 . Less attention has been given to the predictive value of LH for SRR, but our results showed that lower LH levels were more beneficial for sperm retrieval outcomes.…”
Section: Discussionmentioning
confidence: 53%
“…Recently, Major et al conducted a multiple weighted linear regression and found that SRR decreased by 1.0% for every 1.19 mIU/mL increase in FSH. 38 Less attention has been given to the predictive value of LH for SRR, but our results showed that lower LH levels were more beneficial for sperm retrieval outcomes. One possible reason is that high levels of gonadotropins in plasma lead to downregulation of FSH and LH receptors in Sertoli and Leydig cells, and Sertoli and Leydig cells become insensitive to gonadotropins, resulting in poor testicular spermatogenesis.…”
Section: Discussionmentioning
confidence: 53%
“…4 Existing meta-analyses highlight the superiority of MD-TESE over conventional TESE and percutaneous TESA in men with NOA. 5 A study by Bernie 6 included 15 studies with a total of 1890 patients; MD-TESE was compared with conventional TESE and percutaneous TESA. MD-TESE was 1.5 times more likely (95% CI 1.4-1.6) to result in more successful sperm retrieval than conventional TESE.…”
Section: Our Evaluation Of the Paper Authored By Sakasmentioning
confidence: 99%
“…5 Studies investigating predictive factors for positive surgical sperm retrieval in NOA are far from complete Currently, there are no reliable predictive markers of sperm retrieval rate. 6 The sperm retrieval procedure microdissection testicular sperm extraction (MD-TESE) is the gold standard for sperm retrieval in NOA 7 men but combined with in vitro fertilisation (IVF) comes at a significant cost. It has been estimated that only 30% of studies investigating NOA report live birth rates (LBRs), 8 leaving a significant gap in counselling couples with NOA about their realistic chance of taking home a baby once the diagnosis is confirmed.…”
Section: Introductionmentioning
confidence: 99%